Communication Social Actions of Legislative Candidates in the Election of Representatives in the City of Madiun (Case Studi: Social Exchange of Legislative Candidates to Became DPRD) - Parji; Prasetya, Agus (International Journal of Criminology and Sociology, 2022)
Current social phenomena show that the local democratic process that should be running well and correctly in accordance with its purpose is to increase the participation of the people or community politics to elect their representatives in the Regional Representative Council (DPRD) which has not produced maximum election results legislative as a local political activity is carried out based on Law No. 2 of 2011 which was later revised with Law No. 07/2017 concerning elections which regulates the selection of candidates for DPRD which include selection, ratification, appointment, and in terminating board members of the research council this method uses a qualitative approach, where the focus of research uses a case study approach. The purpose of the study was to determine the social communication actions of a prospective legislative candidate in the legislative general election to elect people’s representatives in the DPRD city of Madiun. This research with a qualitative approach is one of the research procedures that produce descriptive data in the form of speech, behaviour, which can be observed from prospective board members. The data collection technique of this research is observation techniques, documentation through snowball sampling on each DPRD candidate who has become a permanent council candidate. To support the conduct of research, researchers used theoretical studies, among others, social exchange theory, Peter Blau and A Weber’s Social Action Theory. The results of this study highlight that; social, legislative communication actions concerning social behaviour, human social movements and social exchanges occur in the election of members of the City Council of Madiun; namely, there are activities for candidates to install campaign propprovide social assistance and transactional practices between voters and candidates at the end of the campaign.